CORRELATION RESPIRATORY RATE (RR) WITH OXYGEN SATURATION (SpO2) THE CLIENTS HEAD INJURY: THE CLIENTS HEAD INJURY - Chuchum Chuchum Sumiarty (Wijaya Husada, 2020)
Background According to the World Health Organization (WHO) traffic accidents are the cause of the eleventh death accidents worldwide and the most common occurrences of traffic accidents related to fatalities are estimated at 1.25 million people each year. Objective this study is the writer want to know the correlation between respiratory rate (RR) with oxygen saturation (SpO2) on the client’s head injury at PMI hospital Bogor city in 2019. Method Analytical observational with a retrospective approach using Kendall's Tau statistical test was implemented at PMI Hospital Bogor city on 18 August - 03 September 2019 with 33 respondents. This study used a sampling technique with total sampling, the instrument used the observation sheet. Result shows that of 33 respondents, who have a normal RR 12 respondents (36%), and who have takipneu 21 respondents (64%), while those who have a normal SpO2 are 17 respondents (52%), hypoxia 16 respondents (48%). The results of the study used Kendall's Tau statistical test showing the results of P value (0,000) <α (0.05) and OR value 27.500. Conclusion in this study there is a correlation between Respiratory Rate (RR) with Oxygen Saturation (SpO2) on client head injury. Suggestion this research is expected being a suggestion for hospital as a form to improving the quality of emergency nursing services in handling cases of Respiratory Rate (RR) with Oxygen Saturation (SpO2) in head injury clients.